Meta-Analysis the Effect of Urinary Tract Infection in Pregnant Women on Prematurity and Low Birth Weight - Wulandari, Rizqi Amalia; Budihastuti, Uki Retno; Murti, Bhisma (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2021)
Background: During pregnancy there are physiological changes associated with the pregnancy process that can cause urinary tract infections caused by the enlargement of the uterus, decreased urine flow through the ureters and decreased bladder tone during pregnancy. So that healthy pregnant women become vulnerable to serious complications in the urinary tract and will have an impact on the mother and baby who will be at great risk of causing premature birth and low birth weight. This study aims to estimate the magnitude of the effect of urinary tract infections in pregnant women on premature birth and low birth weight. Subjects and Method: This study is a systematic review and meta-analysis conducted with PRISMA flow diagrams. Search articles through journal databases including: Google Scholar, MEDLINE/PubMed, Science Direct, Spinger Link and Directory of Open Access Journal (DOAJ) by selecting articles published in 2005-2021. The keywords used were “Urinary Tract Infection Pregnancy” AND “Preterm Labor”, “Urinary Tract Infection Pregnancy” AND “Low Birth Weight”, “Urinary Tract Infection Pregnancy” AND “Preterm Labor” AND “Low Birth Weight” AND “adjusted Odds Ratio